Use of Distance Education by Religions of the World to Train, Edify and Educate Adherents - Rogers, P. Clint; Howell, Scott L. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Islamic, Hindu, Buddhist, Baha'i, Jewish, and Christian organizations are all experimenting with distance education for various reasons and to different extents, due to religious, economic, and political factors. Religious institutions worldwide are not only turning to the World Wide Web (WWW) to place information concerning religious beliefs and provide virtual services for their constituents but are also getting more involved in formally educating their members at a distance. This paper will document some of these educational efforts and the reasons behind the expanding use of distance education by several of the major religious institutions for training, edifying, and educating their religious adherents.